Food consumption and nutrition: FCND research themes brochure - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The Food Consumption and Nutrition Division (FCND) takes the lead at IFPRI on research to improve economic access to food and the ability to harness food for growth and nutrition. The FCND research program asks: How do policies and programs affect community, household, and individual food security; and What do poor individuals do themselves to generate income, secure food, and ensure good nutrition and health, and which institutions facilitate and constrain the poor in these endeavors? FCND research and outreach activities are organized into five research themes, each conducting research in a number of countries on a common set of policy issues: Rural Finance Policies for Food Security of the Poor; Urban Challenges to Food and Nutrition Security; Gender and Intrahousehold Aspects of Food Policy; Targeted Interventions to Reduce and Prevent Poverty; Agricultural Strategies for Improving Availability of Micronutrients.